2x=(90/4)

Simple and best practice solution for 2x=(90/4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x=(90/4) equation:



2x=(90/4)
We move all terms to the left:
2x-((90/4))=0
We add all the numbers together, and all the variables
2x-((+90/4))=0
We multiply all the terms by the denominator
2x*4))-((+90=0
Wy multiply elements
8x^2+90=0
a = 8; b = 0; c = +90;
Δ = b2-4ac
Δ = 02-4·8·90
Δ = -2880
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 6m+3=29; | | (7-x)5+7x=73 | | 10=-4p-6p | | 6y+1=3y+28 | | 15/18y+1=−6/18y+10/18 | | 5/6y+1=−1/3y+5/9 | | (x)=−3x^2+75 | | −2x^2−9+107=0 | | 160(x-3)=100x | | (3-4x/6)-(2x-3/8)=2-x | | y-4.7=18.6 | | 120=0.30-6x | | -8a-1=2-5a | | 4x+4x^2+3+3x=0 | | 4x+4x^2+3+3x=) | | X+5x-15=x+235 | | 1.4x+3=17 | | 6x+3=9+8x | | 5x+3=6x+15 | | 2x,-3=0 | | 5/6x=8=-11 | | (5x+9x+6x)-(-9x-20x-+6x)=0 | | 5/6x+8=-11 | | 3x2-6x+12=0 | | -2(4s-5)-10=-2(6s+4)-2 | | (9x^2+12)-(7x^2+10x+13)=0 | | -37=5v-7 | | x=15-9+2 | | 3(6x-2)=-2(5x-4) | | 8+2/3(6x+30)=8 | | Y=20610+26x | | (8)/(5)a=-6 |

Equations solver categories